Developing Subak Capacity in Facing the Challenges of Modern Agriculture and Climate Change in Bali - Rusmana, I Putu Edi (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: This study aims to analyze the challenges faced by the traditional Subak irrigation system in Bali in facing the development of modern agriculture and the impacts of climate change, and to identify strategies that can be used to overcome these challenges. Research methods: The research method used is a qualitative normative approach with analysis of literature, policy documents, and relevant secondary data. This study also involves a descriptive-evaluative approach to describe the condition of Subak and the potential and constraints it faces. Results and discussion: Subak needs to adopt modern agricultural technology that is in accordance with local wisdom values, as well as increase the capacity for adaptation to climate change through adjustments to cropping patterns, application of environmentally friendly technology, and strengthening institutions. Implication: The implication of this study is the need for comprehensive policy support and ongoing education for farmers to ensure the sustainability of Subak as a traditional irrigation system that is able to face the challenges of modernization and climate change, so that it continues to play a role as the main foundation of agriculture in Bali.